2019
DOI: 10.1136/bmjopen-2019-029522
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exposure to the natural environment and recovery from hip or knee arthroplasty: a New Zealand retrospective cohort study

Abstract: ObjectivesDetermine whether patients who live in greener and more walkable neighbourhoods live longer, and take fewer opioids, following hip or knee arthroplasty.DesignRetrospective cohort study.SettingResidential environment following surgery at one of 54 New Zealand hospitals.ParticipantsAll people who received a total hip or knee arthroplasty at a publicly-funded hospital in New Zealand in 2006 and 2007 (7449 hip arthroplasties and 6558 knee arthroplasties).Primary and secondary outcome measureTime to all-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…What are the consequences of losses of daylight/weather/seasonal effects due to urban densification, loss of daylight recreation areas, daylight restriction due to high buildings etc. on mood, health and quality of life [69,[220][221][222][223]?…”
Section: Latitudementioning
confidence: 99%
“…What are the consequences of losses of daylight/weather/seasonal effects due to urban densification, loss of daylight recreation areas, daylight restriction due to high buildings etc. on mood, health and quality of life [69,[220][221][222][223]?…”
Section: Latitudementioning
confidence: 99%
“…These studies were conducted in China (6 studies), 31,[37][38][39][40][41] Japan (3 studies), [42][43][44] Hong Kong (2 studies), 29,45 South Korea (2 studies), 46,47 Taiwan (2 studies), 48,49 and New Zealand (2 studies). 50,51 One study each was reported from Thailand, 52 Vietnam, 53 and Australia. 30 Only eight studies were conducted in low-and middle-income countries (Table 1 and Supplementary Table 1).…”
Section: Peer Reviewmentioning
confidence: 99%
“…residential surrounding greenness examined in the studies encompassed public open spaces such as parks, natural spaces, and bushland, 30 urban green spa ces, 39,41,[45][46][47][48][49] trees, grass, plants, and natural vegetation, 29 woodland and farmland, 44 walkable green streets and spaces, 42 parks, gardens, and green areas, 40 natural areas such as parks, beaches, and fields, 50 parks, forests, wetlands, and grasslands, 38 grass, forests, and parks, 52 vegetation and city parks, 43 green and walkable neighbourhoods, 51 and green spaces of urban or rural residence areas. 31,37,53 in 10 studies, the exposure to greenness was measured by normalised The influence of residential greenness on mortality in the Asia-Pacific region: a systematic review and meta-analysis The influence of residential greenness on mortality in the Asia-Pacific region: a systematic review and meta-analysis…”
Section: Definition and Measurement Of Residential Greennessmentioning
confidence: 99%
See 1 more Smart Citation
“…Alienation from nature What are the consequences of losses of daylight/weather/seasonal effects due to urban densification, loss of daylight recreation areas, daylight restriction due to high buildings etc. on mood, health and quality of life [69,[220][221][222][223]?…”
Section: Latitudementioning
confidence: 99%